A Cardiogenic Shock due to an Acute MI with LCA Arising from the Right Coronary Sinus Successfully Treated with PCI - Rayyan Jadeed; Klaus Pethig; Dirk Böcker (Case Reports in Cardiology)
Coronary artery anomalies (CAAs) are a diverse group of congenital anomalies with an incidence ranging from 0.17% in autopsy cases to 1.2% in patients undergoing coronary angiography. The left coronary artery (LCA) originating from the right coronary sinus is a very rare CAA with a frequency of 0.03%. We present a very rare case of a cardiogenic shock as a consequence of an acute anterolateral myocardial infarction by a totally occlusive lesion in the long left main stem with a complete LCA arising from the right coronary sinus in an 85-year-old female. This lesion was successfully treated with 2 drug-eluting stents. This is perhaps the first published case about cardiogenic shock due to an acute myocardial infarction associated with this type of coronary anomalies, and it presents a special challenge in the catheter laboratory.